An institutional analysis of the implementation of integrated water resources management in Nigeria - Adeoti, Olusegun (Cranfield University, 2014)
Many studies have investigated Nigeria’s experiences of river basin management. Despite the acceptance of IWRM by the Nigerian Government, findings from the literature demonstrate that there remain significant water management challenges in Nigeria. However, reported research which exposes the forces influencing the implementation of Integrated Water Resources Management (IWRM) in Nigeria remains sparse. This thesis exposes these forces, and most importantly, the environments within which they are embedded by drawing upon theoretical and empirical evidence on the processes required to transfer IWRM from theory to practice. The retroductive logic of enquiry was adopted as a guide and a conceptual framework was developed to illustrate the forces influencing IWRM implementation at the river basin level in Nigeria and the environments within which they are embedded. The conceptual framework formed the basis for the development of the research questions and also informed the choice of neo-institutional theory as a guide to proffer answers to the research questions. The research process employed a qualitative social science approach to provide answers to the research questions and realise the study’s main aim. The study’s theoretical framework followed a string of hermeneutics, phenomenology, and interpretivists philosophies and a case study research strategy to explore issues related to IWRM implementation in both Ogun-Oshun River Basin and Benin-Owena River Basin from different perspectives using multiple sources of evidence – documents, semi-structured interviews, and direct observations. Interviews were conducted with the staff of the River Basin Development Authorities (RBDAs) and other water-related national and international organisations in the selected case river basins in Nigeria. The data obtained were first analysed using textual approach and then followed by variance institutional approach. Findings clearly illustrate that: (i) there were weaknesses in IWRM implementation in Nigeria, and (ii) both institutional (that is, regulative, normative, cognitive, and cultural) and technical (that is, water infrastructure) elements which are located within the macro and the operational environments were the forces that contributed to the weaknesses in IWRM implementation at the river basin level in Nigeria. Consistent with the institutional analysis perspective, to improve IWRM implementation in practice in Nigeria, the study proposed improvements to the regulative institutions to serve as a shock. This study contributes to IWRM and reinforces the importance of institutional and technical elements as potent forces that can enable or constrain the implementation of a water management approach, IWRM.
Keywords: River basin management; IWRM; Institutional analysis; Nigeria